A viable mathematical model for seed moisture prediction in multiple species - Jacob, Sherry R; Jha, Girish K; Singh, Gajab; M B, Arun Kumar (The Indian Journal of Agricultural Sciences, 2019)
Modeling of seed sorption kinetics have been routinely applied for predicting the equilibrium moisture content (EMC ) of processed products and the information is used for determining their drying and storage parameters. Similar information is also valid for the seed industry because moisture content of the stored seed would determine its longevity and quality. But in seed industry, the storage facilities are used for multiple species having distinct physical and biochemical characteristics and there is a need to explore and identify a single mathematical model that can comprehensively predict moisture sorption behaviour of a wide range of species. In the present study, the Modified Henderson model could effectively describe the sorption kinetics of Pea, Okra and Chilli and gave the best fit for the data, when analyzed using mean relative error (MRE, %), standard error of estimate/moisture (SEM) and randomness of residual pattern as observed in the residual plots.